The Influence of Perspective on Perception: Assessing Residue Across Planes of Videofluoroscopy - Jones‐Rastelli, R. Brynn; Crossman, Claire; Price, D'manda; Stal, Frederick; Molfenter, Sonja (The Laryngoscope, 2025)
Objectives (1) To determine whether perception of pharyngeal residue severity differs by view plane on videofluoroscopy. (2) To explore whether the Bolus Clearance Ratio (BCR) can be reliably applied in the anterior–posterior (AP) plane. (3) To investigate the relationship between perception of residue severity and BCR measures across view planes. Methods Images of the same bolus condition in lateral and AP were rated using a simple 5‐point ordinal descriptive scale (none, trace, mild, moderate, severe) by 225 speech‐language pathologists via electronic survey. BCR measures were obtained for the same set of images from four trained raters. Wilcoxon signed‐rank tests and cumulative mixed modeling were used to compare ratings by plane. BCR reliability was calculated using intraclass correlation coefficients. Perceptual ratings were compared with BCR measures using Spearman correlations. Result (1) Perception of residue severity was not consistent across plane in 9/10 image pairs (p < 0.05), with a significant fixed effect of plane on severity rating (β = 0.41; z = 7.27; p < 0.001). The directionality of differences varied by case. (2) Inter‐rater reliability for BCR measures was good across lateral (intraclass correlation coefficient [ICC] = 0.82) and AP (ICC = 0.87) planes, with superior intra‐rater reliability in AP (lateral ICC = 0.85; AP ICC = 0.98). (3) There was a strong positive correlation between perceptual ratings and BCR measures in both planes. Conclusions Perception of pharyngeal residue severity differs between lateral and AP planes with inconsistent directionality raising important questions about the clinical implications of single plane studies. The BCR shows good‐excellent reliability and strong correlation with perception across planes, offering a promising method for cross‐plane quantification. Level of Evidence 3, diagnostic study with a gold standard Laryngoscope, 135:1352–1358, 2025 The objectives of this study were: (1) To determine whether perception of pharyngeal residue severity differs by view plane on videofluoroscopy. (2) To explore whether the Bolus Clearance Ratio (BCR) can be reliably applied in the anterior–posterior (AP) plane. (3) To investigate the relationship between perception of residue severity and BCR measures across view planes. Perceptions of pharyngeal residue severity differ between lateral and AP planes, with inconsistent directionality. The BCR shows good to excellent reliability across planes and correlates strongly with perception of residue severity.